Implementasi Panic Button Berbasis Android Sebagai Bentuk Kewaspadaan, Pencegahan, dan Keamanan Pada Masa Pandemi Covid-19 - Muhammad Syaeful Fajar; Susilo Veri Yulianto; Nisa'ul Hafidhoh; Tri Lestariningsih; MH. Ramdhani Ismar (Direktorat Penelitian dan Pengabdian kepada Masyarakat (DPPM), 2022)
Crimes that are often reported in the mass media make people feel less safe, especially if you look at the number of crimes that occur every year. Based on data from the Central Statistics Agency (BPS) the number of crimes that occurred during the period 2017 – 2019 averaged 300,085 cases annually. Of the many problems that occur, it is necessary to use an appropriate application to disseminate emergency information by considering how the victim reports, the time it takes for the victim to report, and the accuracy of the reporting data. With the development of the Panic Button application, it is hoped that it will make it easier to contact the surrounding community in delivering an emergency. Where the system will send a notification to the user's cell phone and turn on an alarm. In its development, the author uses the Global Positioning System to get location coordinates, Firebase Push Notification as a notification message sender and Arduino Wemos D1 as an alarm system driving mechanism.